A case study amyloid arthropathy in silver chickens - Jimenez, Vingelle Bautista; Van Eck, Jo HH; Tooten, Peter CJ; Upragarin, Narin (2009)
Thirteen thirty-week-old layers (Lohman Silver)that showed lameness were necropsied. Sera were collected and bacterial isolation was performed. Gross examination revealed amyloid deposits in the joints. The lesion was limitedly present only in knee joints.Enterococcus faecalis was the predominant microorganism isolated. Tissue from joints, liver, spleen, and kidney were positive with anti-chicken AA antisera using EnvisionTM + Peroxidase. SAA levels were generally increased in amyloidotic sera using direct ELISA but relatively low compared to acute phase sera. Moreover, Western Blot analysis revealed a low signal of SAA. From These findings, it was concluded that the birds suffered from amyloid arthropathy.
Keywords: Silver (Chicken); Amyloid arthropathy; Mindanao studies; Chicken--Diseases